Thiophene Ring-Opening Reactions V. Expedient Synthesis of 1,3,4- Thiadiazoline-Sulfanyl[1,3]thiazin-4-one Hybrids - Jarrar, Abdullah K.; El-Abadelah, Mustafa M.; Sabri, Salim S.; Zahra, Jalal A.; Hamdan, Mohammad S. (Letters in Organic Chemistry, 2022)
The preparation of 6-chloro-5-nitrothieno[3,2-e][1,3]thiazin-4-one incorporating 2-(Nmorpholinyl) moiety is achieved via a conventional route. Interaction of the latter substrate with a set of N'-(aryl) benzothiohydrazides 1a-f, in the presence of triethylamine, led to a thiophene ring-opening process with the consequent generation of the respective thiolate salts 8a-f. Alkylation of the latter, using methyl iodide or allyl chloride, generated the respective novel 1,3,4-thiadiazoline-6-sulfanyl-1,3- thiazin-4-one hybrids, the structures of which were verified by HRMS and NMR spectral data.
Keywords: thieno[3; 2-e][1; 3]thiazin-4-one